(untitled) (Research, Society and Development, 2022)
Although artisanal fishing is one of the main subsistence activities of families and communities in the Amazon region, its invisibility of production is still an obstacle to be overcome, especially within its class representative entities. With this, the present research aimed to characterize artisanal fishing on two islands (Tabatinga and Sirituba) located in the municipality of Abaetetuba - PA, as a way of highlighting the importance of this activity for the local riverside communities and the state as a whole. The study is characterized as descriptive, of a quantitative and qualitative nature, where a questionnaire was applied to 30 fishermen from each island. Thus, it was possible to identify that the artisanal fishermen of the two islands have similar demographic characteristics, where the customs, practices and relationships between the family, traditions and fishing are maintained in each generation. The fish is obtained in a traditionally artisanal way, using methods and artifacts inherited from previous generations. Mapará is the most consumed fish among the participants, who use the fishing activity for food and commercialization. However, socio-environmental problems are identified that cause disorders and changes in the way and customs with which fishermen carry out fishing, and in some cases it is necessary to move them to carry out the fishing activity away from their family and home. In this way, we point out the need for planning actions that alleviate and support the main problems that plague the fishermen in question.